Effects of endwall profiling near the blade leading edge on the sealing effectiveness of turbine rim seal. (November 2019) - Shuxian, Cheng; Zhigang, Li; Jun, Li
Endwall profiling designed to reduce secondary flow loss may change the local pressure distribution which has an impact on the sealing effectiveness of a rim seal. This paper presents a numerical comparison of the sealing effectiveness of the rim seal and the aerodynamic performance of the blade with five different endwall profiling near the blade leading edge. Three-dimensional unsteady Reynolds-averaged Navier-Stokes (URANS) equations coupled with a fully developed shear stress transport (SST) turbulent model are utilized to investigate the sealing effectiveness and the flow characteristics of turbine rim seal. The numerical method for the pressure field and sealing performance of turbine rim seal is validated on the basis of published experimental data. The total-to-static efficiency of the blade and the minimum sealing rates of the rim seal with five endwall profiling near blade leading edge are compared. The baseline, convex and concave cases are selected to investigate the transient variation of the sealing effectiveness and the flow field in the disc cavity. In comparison with baseline case, the convex endwall makes the high pressure area move forward, increases the mainstream circumferential pressure fluctuation, and reduces the sealing effectiveness. The concave endwall reduces the local pressure and the mainstream circumferential pressure fluctuation, and increases the sealing effectiveness. However, the concave endwall profiling enhances the vortex in the blade passage and increases the secondary flow loss. The flow field near the rim seal with different endwall profiling is illustrated and analyzed.